Application of Non-Newtonian Liquid Membranes to Extract Nicotine from Tobacco - Guo*, Zhifeng; Zhang, Xiaoxuan; Wu, Xiaoyang; Dong, Jingjing (Asian Journal of Chemistry, 2014)
In the present study, a stable emulsion liquid membrane was prepared through adding polystyrene in a membrane phase. The emulsion liquid membrane extraction system was composed by the membrane phase (kerosene, Span80 and polystyrene) and the strip phase (acidic aqueous solution). The feed phase was nicotine basic aqueous solution or tobacco extractant. A water-in-oil-in-water (abbreviated W/O/W) is formed as dispersing the emulsion liquid membrane with added polystyrene additive in the feed phase, which will be the non-Newtonian. Comparing with the emulsion liquid membranes without polystyrene, the emulsion liquid membranes with polystyrene extended the extraction time from 5 to 8 min, which illustrates that adding polystyrene helps improve the stability of emulsion liquid membranes. The application of using these emulsion liquid membranes for extraction nicotine from tobacco shows the extraction efficiency of nicotine is higher than using liquid-liquid extraction.